2014
DOI: 10.1186/1556-276x-9-83
|View full text |Cite
|
Sign up to set email alerts
|

Seed/catalyst-free growth of zinc oxide nanostructures on multilayer graphene by thermal evaporation

Abstract: We report the seed/catalyst-free growth of ZnO on multilayer graphene by thermal evaporation of Zn in the presence of O2 gas. The effects of substrate temperatures were studied. The changes of morphologies were very significant where the grown ZnO structures show three different structures, i.e., nanoclusters, nanorods, and thin films at 600°C, 800°C, and 1,000°C, respectively. High-density vertically aligned ZnO nanorods comparable to other methods were obtained. A growth mechanism was proposed based on the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 35 publications
2
33
0
Order By: Relevance
“…In recent years, the hybrid structures of zinc oxide (ZnO) nanostructures on graphene have attracted much attention because the nanostructures can offer additional functionalities to graphene for realizing advanced nanoscale applications [ 1 , 2 ]. This is due to the superior properties of nanostructures such as quantum confinement effects and high surface-to-volume ratio [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the hybrid structures of zinc oxide (ZnO) nanostructures on graphene have attracted much attention because the nanostructures can offer additional functionalities to graphene for realizing advanced nanoscale applications [ 1 , 2 ]. This is due to the superior properties of nanostructures such as quantum confinement effects and high surface-to-volume ratio [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…[185][186][187][188][189][190] Most studies on the ZnO/graphene hybrid structures have been focused on their structural morphology and electronic properties. 191,192 Recently, Xiang et al 193 rst proposed a three-component composite, TiO 2 /graphene/MoS 2 , containing 0.25 wt% graphene. The results showed that graphene acts as an electron reservoir and MoS 2 can act as a source of active adsorption sites to achieve a highly efficient synergetic H 2 evolution at the rate of 165.3 mmol h À1 , which is 17 times that of TiO 2 /MoS 2 .…”
Section: Theoretical Achievements For the Development Of Nanophotocatmentioning
confidence: 99%
“…Many studies have been conducted on the development of semiconducting material/graphene hybrid structures using either gas phase [223][224][225][226] or liquid phase techniques. 185,186,191,227 Hou et al 228 have developed a CdS QDs/graphene/ZnIn 2 S 4 system that exhibits highly efficient H 2 production due to the high hydrothermal stability and efficient electron transfer. Graphene can also play a role as a co-catalyst and constitutes a synergistic effect with the other co-catalyst to improve the photocatalytic efficiency.…”
Section: Theoretical Achievements For the Development Of Nanophotocatmentioning
confidence: 99%
“…With this regard, the growth of Ga-based compound materials on graphene seems to be feasible. Recently, we have demonstrated the growth of several kinds of materials such as germanium (Ge) thin film [29], silicon carbide (SiC) thin film [30], and zinc oxide (ZnO) nanostructures [31][32][33][34][35] with considerably good properties directly on graphene without any use of seed or catalyst.…”
Section: Introductionmentioning
confidence: 99%